Pencegahan Kejadian Stunting Melalui Analisis Faktor pH Kualitas Air Minum Rumah Tangga - Tisar Dewi Pratiwi; Yunita Widia Putri; Dewi Rakhmatia Nur (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Stunting is a social urgency in Indonesia that affects the development of health and intelligence of children. Based on data from the Ministry of Home Affairs the percentage of stunted toddlers in Bandar Lampung City is 0.8% or 520 toddlers of the 63,998 toddlers in all Bandar Lampung City Districts. Clean water is one of the causes of stunting. To find out the level Cleanliness of drinking water can be done by measuring the pH value using litmus paper. However, pH measurements are more accurate using Primary standard for calibrating glass electrodes and pH meters. This research aims to map and analyze the pH factors of drinking water as well as the mineral content of the water, so it is hoped that it can be used as a reference or rejection measure against the Bandar Lampung City government and the local community planning health services and human resources. The method This research carried out a survey the pH and metal content of water used for drinking and cooking in households in 19 sub-districts. The results of pH and electrolysis testing showed that the pH and water content in Bandar Lampung City varied greatly from 3.61 to 8.5. On the map, 95 measurement points are spread across sub-districts throughout Bandar Lampung City, with data interpolation tending to be colored yellow, green and blue. This is predicted because several areas in Bandar Lampung City are well maintained so that water quality is maintained and several other areas have experienced pollution and the water in these areas contains dangerous chemicals and even heavy metals. Keywords: Water, Toddlers, pH, Mineral content of water, Stunting.